A vision-based machine accuracy measurement method. Issue 1 (2020) - Irino, N.; Shimoike, M.; Mori, K.; Yamaji, I.; Mori, M.
Abstract: Accuracy measurement in working space is crucial in the evaluation of machine tools and 3D-CMMs. Though tracking type laser interferometers are widely used in the measurements, there are some problems: The devices are inevitably expensive due to their continuous tracking mechanism; Requiring several hours to measure the entire working space. To solve these problems, A vision-based accuracy measurement system, which utilizes the sequential multi-point method, is developed. The system can measure the entire working space within one hour. The measurement accuracy of the system is equivalent to conventional systems. Verification experiments are conducted on a machining center.